2018
DOI: 10.1159/000485043
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Perfusion Derived Blood-Brain Barrier Permeability Does Not Yet Improve Prediction of Hemorrhagic Transformation

Abstract: Introduction: Hemorrhagic transformation (HT) in acute ischemic stroke can occur as a result of reperfusion treatment. While withholding treatment may be warranted in patients with increased risk of HT, prediction of HT remains difficult. Nonlinear regression analysis can be used to estimate blood-brain barrier permeability (BBBP). The aim of this study was to identify a combination of clinical and imaging variables, including BBBP estimations, that can predict HT. Materials and Methods: From the Dutch acute s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…25 Similar results were reported by further studies (LOE: IV). 26,27 Large-vessel obliteration and poor collateral state on CTA have been shown to be associated with higher risk of HT (LOE: IV). 24,26,28 In 2012 Lin et al reviewed three variables in CTA: (1) distal ICA and/or M1 segment of the MCA, (2) ASPECTS and (3) collateral score.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 Similar results were reported by further studies (LOE: IV). 26,27 Large-vessel obliteration and poor collateral state on CTA have been shown to be associated with higher risk of HT (LOE: IV). 24,26,28 In 2012 Lin et al reviewed three variables in CTA: (1) distal ICA and/or M1 segment of the MCA, (2) ASPECTS and (3) collateral score.…”
Section: Discussionmentioning
confidence: 99%
“…High PS has increased risk of occurrence of HT after AIS (LOE: IV). 27,34,37,38 A recently published high LOE (I) systematic review found the CTP imaging appearance suggestive of high BBB permeability, and acute severe hypoperfusion (i.e. CBV < 0.5 ml/100 g; rCBV ¼ 1.09; rCBF < 0.48; Tmax > 14 s; rMTT.1.3; TTP 0.27 s) are highly sensitive and predictive for the risk of HT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perfusion CT can also generate BBBP maps that can help in the identification of patients at risk of HT ( 65 , 171 , 172 ), but its relevance compared to other predictors has been contested ( 173 ).…”
Section: Blood–barrier Permeability Evaluation In the Early Detectionmentioning
confidence: 99%
“…Computed tomography perfusion-derived bloodbrain barrier permeability does not yet improve the prediction of hemorrhagic transformation [4].…”
mentioning
confidence: 99%